Ethylmalonic Encephalopathy: a literature review and two new cases of mild phenotype - KILAVUZ, SEBİLE (My University, 2023)
Background Ethylmalonic encephalopathy (EE) is a rare intoxication-type metabolic disorder with multisystem involvement. It is caused by mutations in ETHE1, which encodes the ETHE1 enzyme in the mitochondrial matrix that plays a key role in hydrogen sulfide ( H2S) detoxification acting as a sulphur dioxygenase. Results This review focuses on the clinical, metabolic, genetic and neuroradiological features of 70 reported cases, including two new cases. The common manifestations of EE are psychomotor regression, hypotonia, developmental delay, petechia, pyramidal signs, chronic diarrhoea, orthostatic acrocyanosis and failure to thrive, respectively. A significant difference was found in EMA and C4 levels (p=0.003, p=0.0236) between classical and mild phenotypes. Urinary EMA, C4 and C5 levels were found to exhibit normal values in milder cases during attack-free periods. The most common ETHE1 gene homozygous state mutations were (p.R163Q) (c.488G>A), exon 4 deletion, (p.R163W)(c.487C>T), (p.Glu44ValfsTer62) (c.131_132delAG) and (p.M1I)(c.3G>T) mutations, respectively. Fifty-two patients underwent cranial MRI. Basal ganglia signal alterations were detected in 42 cases. Of the 70 cases, eight had a mild phenotype and slow neurological progression with low levels of ethylmalonic acid (EMA) and C4 acylcarnitine. The current age of alive patients in the published articles with mild phenotype was significantly higher than the classical phenotype. (p=0.002). Reducing the accumulation and inducing detoxification of sulfide is the main long-term treatment strategy for EE, including metronidazole, N-acetylcysteine (NAC), dietary modification, liver transplantation and continuous renal replacement therapy (CRRT). Conclusion Measuring EMA and C4 acylcarnitine during metabolic attacks is critical to diagnosing EE, allowing for early treatment initiation to prevent further encephalopathic crises. Experience with liver transplantation, diet and CRRT, is currently limited. An early multidisciplinary approach with combination therapies is vital to prevent irreversible neurological damage. Keywords: Ethylmalonic encephalopathy, ETHE1, Mild, Spastic paraparesis, Ethylmalonic acid, H2S
Keywords: Tıp; Dahili Tıp Bilimleri; Dermatoloji; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Dermatology; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Psikiyatri; DERMATOLOJİ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; PSYCHIATRY; DERMATOLOGY; CLINICAL NEUROLOGY; Nöroloji (klinik); Psikiyatri ve Ruh Sağlığı; Neurology (clinical); Psychiatry and Mental Health; ETHE1; Ethylmalonic acid; Ethylmalonic encephalopathy; H2S; Mild; Spastic paraparesis